Board gender diversity and Voluntary Greenhouse Gas Emission Disclosure in Sri Lanka - Thaneshan, G.; Tharsika, K.; Varanitha, S. (University of Jaffna, 2024)
Purpose: Greenhouse gas emissions are acknowledged as a major contributor to global climate change. Recently, stakeholders are increasingly concerned about environmental issues and expect companies to provide comprehensive information regarding environmental practices and impacts. This paper explores the relationship between board gender diversity and the voluntary disclosure of greenhouse gas emissions among companies in Sri Lanka. Design/Methodology/Approach: The paper utilizes panel data collected from non- financial listed companies in Sri Lanka for the period from 2020 to 2024. The final sample includes 50 firms and 250 firm-year observations, with greenhouse gas emissions disclosure serving as the dependent variable and board gender diversity as the independent variable. Findings: Research indicates that companies with greater gender diversity on their boards demonstrate a positive and statistically significant (R = 0.92, p < 0.001) impact on the voluntary disclosure of greenhouse gas emissions in Sri Lanka. The outcome of regression claims that gender diversity explains 22% of the variance in greenhouse gas emissions disclosure (R2 = 0.22, F = 28.93, p < 0.001). Other factors, such as other corporate governance, may account for the remaining 88% of a company's disclosure. This aligns with the resource dependency theory that diversity enhances a board's capacity for effective advising and monitoring. Diverse leadership fosters a broader range of perspectives and experiences, often translating into a stronger focus on sustainability initiatives. As a result, board gender diversity prioritizes transparency and accountability, leading to improved voluntary disclosure of greenhouse gas emissions. Research limitations: The study is limited to companies listed on the Colombo Stock Exchange and may not represent all sectors or unlisted firms in Sri Lanka. Implications: The findings suggest that enhancing board gender diversity can drive better voluntary greenhouse gas emission disclosure practices. Policymakers and corporate leaders should promote gender diversity in leadership roles as a strategy to improve environmental reporting and foster a culture of accountability within companies.
Keywords: Board diversity; Climate change; Greenhouse gas emissions; Disclosure; Sri Lanka